Hepatoprotective activity of aqueous extract of the leaves of Hyptis suaveolens (l.) Poit on acetaminophen Induced hepatotoxicity in Rabbits - Babalola, O. O.; Ojo, O. E; Oloyede, F. A (2014)
The study was designed to evaluate the possible hepatoprotective activity of the pretreatment with aqueous extract of the leaves of Hyptis suaveolens on acetaminophen induced hepatotoxicity in rabbits. Albumin, total protein, total globulin, alanine transaminase aspertate transaminase and catalase in the blood plasma and liver were assayed as biochemical markers of hepatotoxicity and possible associated oxidative stress. Plasma and total liver proteins, albumin. globulin concentrations were determined using standard spectrophotometric methods also the activities of alanine transaminase, aspertate transaminase and catalase in the plasma and liver homogenates were determined by standard techniques. The maker enzymes show significant elevation in acetaminophen treated animals; these were significantly reduced toward an almost normal level in animals pretreated with aqueous extract of the leaves of Hyptis suaveolens. The reduction was observed for the concentrations of total protein and albumin. This showed that aqueous extract of the leaves of Hyptis suaveolens in addition to many of its numerous reported bioactivity probably possesses hepatoprotective potentials on acetaminaphen induced liver damage.